Analysis Strength And Endurance Of New Students Sports Education Faculty In Teacher Training And Education, Muhammadiyah University Of Surakarta - Nurhidayat Nurhidayat; Eko Sudarmanto; Gatot Jariono; Ardhian Tomy Kurniawan; Fathurrahman Fathurrahman (Universitas Bengkulu, 2021)
The purpose of this study is to analyze the strength and endurance of new students of FKIP sports education at The University of Muhammadiyah Surakarta in 2020 which includes arm muscle strength, abdominal muscle strength, and maximum oxygen volume ability (VO2max). This research is descriptive research using the closeness of quantitative research types. The sample in this study is all new students of FKIP UMS sports education in 2020 numbered 141 people. Teknik collection uses push-up tests to measure arm muscle strength, sit-up tests to measure abdominal muscle strength, and MFT (multistage fitness test) running tests. Teknik data analysis uses frequency descriptive analysis with the help of excel 2019 Microsoft software. The results of this study can be concluded: (i) the strength of new students POR FKIP as a whole is a moderate category obtained from the push-up test with a percentage of 36.88 %; (ii) sit up tests with a percentage of 36.17%, and (iii) endurance freshmen POR UMS category good category with a percentage of 34.75%. But in this study, it is necessary to pay attention to the quality of other physical conditions, namely flexibility, agility, speed, and psychology of students and those related in this study on physical tests and sports ability.